Displasia ektodermal tipe hipohidrotik pada seorang anak bayi tiga tahun - I Putu Arie Sasmita; Luh Made Mas Rusyati (Intisari Sains Medis, 2019)
ABSTRACTIntroduction: Ectodermal dysplasia (ED) is a rare genetic disorder characterized by defect in two or more ectodermal structures such as teeth, hair, nails and sweat glands. Ectodermal dysplasia divided into 2 types, which is hidrotic and hypohidrotic. The hypohidrotic type was found in 80% of cases. There is no specific treatment for this disorder, which is more of a symptomatic measures depends on the structure involved.Case: A 1 year old male, Balinese, consulted from Department of Pediatrics to Department of Dermatovenereology with the chief complaint of dry skin, absence of sweat, teeth, scalp hair and eyebrow since birth. Recurrent fever present especially in hot climates. No growth abnormalities. No history of incest between parents. His grandfather also complained about the same symptoms, which are sparse hair and decreased sweating. General examination revealed frontal bossing, saddle nose, prominent chin and anodontia. Dermatologic examination revealed multiple hypopigmented macules, well defined margin, oval-round shaped, size Ã¸ 0,5-1 cm, distributed over entire skin and anhidrosis. Department of Dermatovenereology gives moisturizer every 12 hours topically. Department of Pediatrics gives zinc tablets, 20 mg every 24 hours orally.Conclusion:The diagnosis of ED was mainly clinical. Treatment is symptomatic and effective education is needed to increase patient's quality of life. Early fetal detection can be performed if there is a risk in the family. Currently, there is a team joined under SIDIC program in Sanglah Hospital whose main purpose is to detect and prevent congenital disorders early.